Interlobate esker aquifer characterization by high resolution seismic reflection method with landstreamer in SW Finland - Elina Ahokangas; Joni Mäkinen; Aki Artimo; Antti Pasanen; Heikki Vanhala (Elsevier B.V., 2022)
The Virttaankangas interlobate esker with 100 m thick sediments has a complex depositional history. It is one of the largest groundwater reserves in Finland and hosts a managed artificial recharge plant providing potable water for the 300,000 inhabitants of the Turku region. We researched the characteristics of the esker aquifer both on a major fracture valley and on an esker ridge with a low groundwater table. This study presents the results of the first landstreamer-based high-resolution seismic reflection survey in Finland conducted in 2011. The esker core (main aquifer) position was delineated accurately throughout the entire area with continuous seismic data compared to a previous sedimentological model, gravimetric data and reference drillings. New features related to the widening of the coarse-grained unit of the esker core as well as a previously unknown daughter esker adjacent to the main esker core were revealed. These new findings are in agreement with the existing 3-D hydrogeological model. Our research provides valuable data on the high-resolution seismic reflection surveying of thick interlobate glaciofluvial deposits on two areas with differing bedrock topography on crystalline basement rocks.